2013
DOI: 10.1002/ajoc.201200136
|View full text |Cite
|
Sign up to set email alerts
|

Preactivation: An Alternative Strategy in Stereoselective Glycosylation and Oligosaccharide Synthesis

Abstract: The multifaceted biological importance of carbohydrates has made them very popular targets in modern synthetic chemistry. Great progress has been made in stereoselective glycosylation methods and the construction of complex oligosaccharides. This Focus Review highlights the versatile applications of preactivation strategies in stereoselective glycosylation and oligosaccharide synthesis. Recent advances in synthetic methods, such as 4,6-O-benzylidene-acetal-directed b-mannosylation, the 1,2-cis-glycosylation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 172 publications
(100 reference statements)
1
26
0
Order By: Relevance
“…These nucleophilic additives or reactivity modulators react with the activated donor to form a new covalent species (see Figure 1 ). 6 Various additives have been probed over the years, including sulfides, 7 sulfoxides/sulfinamides, 8 phosphine oxides, 9 amides and formamides 10 and iodide based reagents 11 and stereoselective 1,2- cis -glycosylation procedures have been reported based on their use. The most often invoked mechanistic rationale to account for the observed stereoselectivity involves the generation of a stable α-covalent species (often identified and characterized by NMR spectroscopy), that is in equilibrium with its less stable and more reactive β-counterpart (often not detected by NMR), following an in situ anomerisation kinetic scenario as first introduced by Lemieux and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…These nucleophilic additives or reactivity modulators react with the activated donor to form a new covalent species (see Figure 1 ). 6 Various additives have been probed over the years, including sulfides, 7 sulfoxides/sulfinamides, 8 phosphine oxides, 9 amides and formamides 10 and iodide based reagents 11 and stereoselective 1,2- cis -glycosylation procedures have been reported based on their use. The most often invoked mechanistic rationale to account for the observed stereoselectivity involves the generation of a stable α-covalent species (often identified and characterized by NMR spectroscopy), that is in equilibrium with its less stable and more reactive β-counterpart (often not detected by NMR), following an in situ anomerisation kinetic scenario as first introduced by Lemieux and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Given the time window between the activation of donor and the addition of acceptor, this activated intermediate can be affected by adding other molecules, which can in turn affect the overall stereooutcomes of glycosylation reactions. 10 In 2004, Boons and co-workers reported that the a-selectivity of 2-azido-2-deoxy glycosyl donors could be greatly enhanced by the addition of PhSEt. 11 In 2006, Crich and co-workers reported that the additional diphenyl sulfoxide could stabilize the activated sialyl intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…[5] For example, several synthetic strategies make it possible to assembly complex oligosaccharides from carefully selected monosaccharide building blocks using a minimal number of chemical steps. [6] Among these strategies, one-pot multi-step glycosylations, in which several glycosyl donors are sequentially reacted in the same flask, are particularly attractive and can furnish target oligosaccharides without the need for protecting group manipulations and isolation and purification of synthetic intermediates. [6c] Within the past few years, automated solid-phase oligosaccharide synthesis has also substantially advanced.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Among these strategies, one-pot multi-step glycosylations, in which several glycosyl donors are sequentially reacted in the same flask, are particularly attractive and can furnish target oligosaccharides without the need for protecting group manipulations and isolation and purification of synthetic intermediates. [6c] Within the past few years, automated solid-phase oligosaccharide synthesis has also substantially advanced. [7] A host of glycosylating agents, new linker systems, different solid supports and a variety of protecting groups have been carefully evaluated and these efforts have resulted in the first commercially available glycan synthesizer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation